New Approaches in Social, Environmental Management and Policy to Address SDGs - Martinez-Nuñez, Margarita; Latorre-Martínez, Mª Pilar (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book comprises a selection of papers addressing some of the most relevant challenges and opportunities for addressing SDGs from many different perspectives. Papers in this collection cover the most recent lines and approaches of research in addressing SDGs and are all novel propositions that deepen the analysis of environmental, social and governance strategies in the adaptation of the society to meet the 17 SDGs.